Wirtualna obecność, czyli o nowym wymiarze kształtowania tożsamości - Gątarek, Izabela (Pedagogika Społeczna Nova, 2024)
The issues of the proposed analysis are based on the issue of creating a young person’s identity in the 21st century. The development and availability of digital media offers a range of opportunities that cannot be ignored today. However, the basis here seems to be the ability to navigate in the digital world. The subsequent stages of life verify so deeply the entirety of a person’s experiences and experiences that, as a consequence, they require flexibility also in the area of continuous shaping of one’s own internal representation. The development of the COVID-19 pandemic has significantly contributed to the “imposed” need for deeper immersion in the digital world as a result of the introduction of remote work and remote forms of education, at all levels. Restrictions on interpersonal contacts have increased the intensity of using social media, especially in view of the increased need for closeness, fear, and the feeling of being cut off from existing relationships and their forms. The proposed considerations are an attempt to look at the issue of identity creation in the context of the above-mentioned events and the series of consequences they brought.